The effect of caffeine ingestion on skill maintenance and fatigue in épéé fencers - Gregory, K. M.; Bottoms, L. M. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Scientific literature discussing caffeine supplementation is extensive. The ergogenic effect of caffeine through peripheral and central mechanisms on sports performance focuses predominantly on endurance sports [1,2]. Fencing is a high-intensity, intermittent sport demonstrating strong associations between the physical, perceptual and psychological demands of sport required to prevent central and peripheral fatigue [3]. This study aimed to explore the effect of caffeine ingestion on skill maintenance and perceived fatigue following exercise simulating the demands of a fencing competition. Seven elite fencers participated (3 female; 4 male; age 32 ± 6.2 years). Following a maximal test to exhaustion, fencers completed two further trials assessing accuracy and reaction times pre and post a fatiguing protocol designed to simulate the demands of the first round of a fencing competition. The reaction test used was the Stroop test. Skill testing involved 30 lunge-touché movements to hit a target replicating competitive attacks. 500ml placebo or 3mg/kg caffeine supplemented drink was administered after the initial reaction and skill tests in a single-blind crossover design. The fatiguing protocol involved the fencer performing a series of bouncing movements (8 seconds on 9 seconds off) with a standardised number of retreats, arm extensions and lunges. 6 fights were completed with a 6-minute rest between each fight. Capillary blood glucose and lactate levels were measured throughout the protocol and fencers rated their perceived exertion (arms, leg, whole body) using the Borg scale. Statistical analysis was a two-way (Treatment X Time) ANOVA for repeated measures (Minitab 15). There was no overall effect of caffeine on skill maintenance (F(1,24)=0.04; p=0.84), however there were significantly fewer misses during the skill test (F(1, 24)=1.37;p=0.04) in the caffeine trial. No effect of caffeine on the Stroop Test was demonstrated. A significant difference in perceived fatigue for the whole body was observed (F(1,96)= 15.33; p= 0.00) in the caffeine trial with a reduction in Borg scores being reported with caffeine. These results provide some support for maintenance of skill and reduction in perceived fatigue during high intensity intermittent sports. Central mediated mechanisms of caffeine appear to be supported from the results as a primary mechanism. Fencers need to continue to make individual decisions regarding caffeine supplements remaining aware that its use in sport continues to be monitored by WADA.